The Relation Between Emotional States And Coping Styles Among High Risk Students - Mohd Khairul Anuar Rahimi; Kamal Abdul Rahman; Farhana Sabri (Universiti Sains Islam Malaysia, 2024)
This study was conducted to examine the relationship between emotional states and coping styles among high risk students at Hilir Perak district secondary school. Specifically, this correlational study is conducted to investigate the level of emotional states among high risk students which includes: (a) to investigate the level of depression, (b) to investigate the level of anxiety, and (c) to investigate the level of stress. This study was also conducted to identify the coping styles among high risk students and examine the relationship between emotional states and coping styles among high risk students. The quantitative study was done by using a survey research design.. A total of 140 students consisting of Form One to Six students from five secondary schools in the Hilir Perak district were respondents in the study. Depression Anxiety Stress Scale (DASS) was used to measure depression, anxiety and stress levels while the Soal Selidik Gaya Daya Tindak (SSGDT) was used to measure coping styles. Data were analysed using statistical descriptive which include a percentage and mean. Inferential analysis using Pearson r correlation statistical analysis were used for variables to be compared using interval measurement scale. Findings indicate the level of depression and stress for high risk student is at a normal level while the level of anxiety is in a mild level. Correlational analysis indicate that the level of anxiety and stress levels are correlated with their coping style. Therefore, the findings indicate several implication for the study.